2020
DOI: 10.1200/jco.19.01892
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Chimeric Antigen Receptor T-Cell Therapy for Adults With Acute Lymphoblastic Leukemia

Abstract: PURPOSE The anti-CD19 chimeric antigen receptor T-cell therapy tisagenlecleucel (CTL019) has an 81% response rate in children with relapsed or chemotherapy refractory (r/r) B-cell acute lymphoblastic leukemia (ALL). Cytokine release syndrome (CRS) is a life-threatening treatment-related toxicity that limits the full therapeutic potential in adults. We report outcomes for adults with r/r ALL treated with an optimized CTL019 dosing and CRS management strategy. METHODS Adults with r/r B-cell ALL received CTL019 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
169
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 181 publications
(184 citation statements)
references
References 12 publications
8
169
0
Order By: Relevance
“… 7 9 Several groups initiated investigation of CD19-specific CAR T cells as a potential therapeutic option for patients with R/R B-ALL. 10 17 This led to the approval by the Food and Drug Administration of CD19-specific CAR T cells for R/R B-ALL in patients <26 years old. 10 16 Despite this success, the incidence of relapse following treatment with CAR T cells in all patients with R/R B-ALL is unknown and has been reported to exceed 50% in some series, demonstrating a need to improve therapy.…”
Section: Introductionmentioning
confidence: 99%
“… 7 9 Several groups initiated investigation of CD19-specific CAR T cells as a potential therapeutic option for patients with R/R B-ALL. 10 17 This led to the approval by the Food and Drug Administration of CD19-specific CAR T cells for R/R B-ALL in patients <26 years old. 10 16 Despite this success, the incidence of relapse following treatment with CAR T cells in all patients with R/R B-ALL is unknown and has been reported to exceed 50% in some series, demonstrating a need to improve therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Commonly used doses are within the order of magnitude of 10 6 cells/ kg (10 8 cells overall). [1][2][3] Within that dosing range, 3 day fractionated administration of tisacel in adult ALL improved the tolerability of a total dose of 5 9 10 8 cells compared to a single infusion of the same dose, 79 and a dose of 2 9 10 7 cells/kg was too toxic in early trials of liso-cel in ALL. 8 As discussed above, higher CTL019 doses increase the CR rate in patients with CLL without increasing risk of severe AE, but did not show improved OS compared to low dose.…”
Section: Updates In Car T Toxicity Managementmentioning
confidence: 98%
“…8,80 Fractionated administration (10% of total dose on day 1, 30% on day 2, 60% on day 3) allows intra-patient dose modification in the setting of early CRS. 79 Risk adapted preemptive tocilizumab decreases the incidence of severe CRS in pediatric patients with ALL and high tumor burden (≥ 40% marrow blasts) treated with tisacel 81 ; however, prophylactic tocilizumab in adults with NHL treated with axi-cel may increase the risk of neurotoxicity. 82 Other approaches to limit CRS could include prophylaxis with a small molecule, such as the Janusassociated kinase (JAK)-1 antagonist itacitinib, currently under study to limit CAR T AE.…”
Section: Updates In Car T Toxicity Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors have suggested preemptive treatment with tocilizumab, an IL-6 inhibitor, for patients at higher risk of severe CRS due to higher disease burden, which resulted in a trend for less grade 4 CRS events in a cohort treated with this agent (40). Another study, which investigated fractionated doses of CAR-T cells, showed high CR rates with manageable toxicities in the fractionated dose cohort (41).…”
Section: Toxicities Associated With Car-t Therapymentioning
confidence: 99%